Comparative Hybrid Hartree-Fock-DFT Calculations of WO2-Terminated Cubic WO3 as Well as SrTiO3, BaTiO3, PbTiO3 and CaTiO3 (001) Surfaces - Eglitis, Roberts; Purans, Juris; Jia, Ran (MDPI, 2021)
We performed, to the best of our knowledge, the world’s first first-principles calculations for the WO2-terminated cubic WO3 (001) surface and analyzed the systematic trends in the WO3, SrTiO3, BaTiO3, PbTiO3 and CaTiO3 (001) surface ab initio calculations. According to our first principles calculations, all WO2 or TiO2-terminated WO3, SrTiO3, BaTiO3, PbTiO3 and CaZrO3 (001) surface upper-layer atoms relax inwards towards the crystal bulk, while all second-layer atoms relax upwards. The only two exceptions are outward relaxations of first layer WO2 and TiO2-terminated WO3 and PbTiO3 (001) surface O atoms. The WO2 or TiO2-terminated WO3, SrTiO3, BaTiO3, PbTiO3 and CaTiO3 (001) surface-band gaps at the Γ–Γ point are smaller than their respective bulk-band gaps. The Ti–O chemical bond populations in the SrTiO3, BaTiO3, PbTiO3 and CaTiO3 bulk are smaller than those near the TiO2-terminated (001) surfaces. Conversely, the W–O chemical bond population in the WO3 bulk is larger than near the WO2-terminated WO3 (001) surface.---//---This work is licensed under a CC BY 4.0 license.
We greatly acknowledge the financial support via the ERAF Project No. 1.1.1.1/18/A/073. Calculations were performed using Latvian Super Cluster (LASC), located in the Center of Excellence at Institute of Solid State Physics, the University of Latvia, which is supported by European Union Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-Teaming Phase 2 under Grant Agreement No. 739508, project CAMART.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Ab initio calculations; ABO3 (001) surfaces; WO3; hybrid exchange–correlation functionals